Design of Prototype Solar Tracking System Dual Axis Based on Positioning System (GPS) for Energy Optimization on 100WP Solar Panel - Rangga Prayoga, Muhammad; Sunawar, Aris; Djaohar, Mochammad (LPPM Universitas Negeri Jakarta, 2025)
Abstract Static solar panels have a disadvantage in capturing solar radiation intensity optimally because they do not follow the movement of the sun. This study aims to design and develop a GPS-based dual-axis solar tracker prototype to optimize energy on a 100WP solar panel. The system tracks the sun's position in real-time based on azimuth and elevation angles using a stepper motor as an actuator, employing the R&D research method and the ADDIE approach. The results show that the solar tracker increases the energy generated compared to the static system. On December 20, 2024, energy increased by 9.6% after accounting for system power consumption. Meanwhile, on December 18, 2024, the energy increase was 5.11%, and on December 19, 2024, it was 1.0%, but these values were before deducting power consumption. The stepper motor’s power consumption of 16.125Wh over 9 hours of operation affected net energy efficiency. Testing showed a tracking error of 1.74%, with an accuracy rate of 98.26%. This study concludes that the GPS-based dual-axis solar tracker can improve the energy output of solar panels with a high tracking accuracy rate.